Faktor-Faktor yang Mempengaruhi Kehamilan Risiko Tinggi di Klinik Evie Kecamatan Babalan Kabupaten Langkat Provinsi Sumatera Utara Tahun 2024 - Damayanty S; Ade Rachmat Yudiyanto; Indra Agussamad; Rahmi Larasati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Background​ Pregnancy risk tall is dangerous pregnancy​ life Mother or the baby she was carrying . Furthermore number pain or death mother and fetus during pregnancy , childbirth and the postpartum period will happens to everyone pregnancy with factor high risk .​ Pregnancy risky tall can influenced by factors medical and non- medical . Pregnancy risk tall is something pregnancy Where soul and health mother and or baby can threatened . Purpose For know the influencing factors pregnancy risk high at the Evie sub-district clinic babalan regency step 2024. Method Research design used​​ in study This is Descriptive analytic with Retrospective approach . Deep sample study This is all over Mother pregnant women with risk data tall as many as 55 mothers pregnant. Analysis data using analysis univariate and bivariate . From the statistical test results obtained The p value is 0.22 (p<0.005) which is significant There is meaningful relationship​ between Education and pregnancy risk tall . From the statistical test results obtained The p value is 0.000 (p<0.005) which is significant There is meaningful relationship​ between Knowledge with pregnancy risk tall . From the statistical test results obtained The p value is 0.980 (p<0.005) which means None meaningful relationship​ between Attitude with pregnancy risk tall.